Experience of Surgical Procedure in the Management of Sigmoid Volvulus - Pradeep Soni; Santosh Uddesh; Rahul Bhargava (International Journal of Medical Research and Review, 2015)
Introduction: Sigmoid Volvulus is the most common type of volvulus, accounting for 75 to 90% of all volvulus. Most common presenting symptom is abdominal pain, distension and constipation. Numerous surgical and non-surgical treatments have been described to relieve this condition. The primary objective of the study is to demonstrate the most suitable surgical procedure for management of patients with sigmoid volvulus presented in emergency.Method: Retrospective study was carried out in the Department of surgery from January 2010 to December 2014. 58 patients with sigmoid volvulus admitted in emergency ward, 55 patients were included in the study and 3 patients excluded. Comparison was done with respect to mortality and early morbidity associated with definitive surgical procedures. (Hartmann’s procedure versus resection and anastomosis with lord’s dilatation).Result: In all patients after investigations and resuscitation surgical treatment was done. Hartmann’s procedure was done in 16 patients (29.09%), primary resection and anastomosis with lord’s dilatation was done in 39 patient (70.90%). 3 patient died before any intervention were not included in study. Over all mortality was 21.81% in the study.Conclusion: Resection and anastomosis with lord’s dilatation is procedure of choice in viable bowel while Hartmann’s procedure is procedure of choice in gangrenous bowel or when the condition of patient is poor.